Texts All the Way Down: The Intertextual Networks Project - Ash Clark; Sarah Connell (Journal of the Text Encoding Initiative)
This paper shares the Women Writers Project’s newest publication, Women Writers: Intertextual Networks, which supports new insights into women’s engagements with print culture during the watershed period of the sixteenth to the nineteenth centuries. With the Intertextual Networks interface, users can discover the many ways that pre-Victorian women writers engaged with and helped to produce early literate culture through their citations, quotations, references, allusions, and more. To create this resource, the WWP team identified all of the texts referenced from within the Women Writers Online collection, and linked these to a bibliography which currently contains more than 4,000 items. The Intertextual Networks interface includes 12,000 quotations, 7,000 citations, 5,000 titles, and hundreds of other forms of intertextuality, described by the WWP as “intertextual gestures.” Owing to its size, this project can offer a model for large-scale bibliographic data wrangling among a complex set of primary sources. This paper shares insights and challenges from this project, discussing strategies for modeling, enabling discovery, and revealing complex layers of textual data and textuality among not only a primary corpus but also a related collection of texts.